KOMUNITAS SWASEMBADA BEBAS POLUSI KARBON DI RUSUN TANGERANG SELATAN - Hansen Jeremy Rahardjo; Suwandi Supatra (Jurusan Arsitektur dan Perencanaan, 2021)
Earth's ecologies are getting worse every year, our earth's temperature has reached 1.2 degrees Celsius hotter than the pre-industrial times, the rapid development of humans seems to have